Near-surface modification of defective KTaO3 by ionizing ion irradiation. (1st July 2021) - Velişa, G; Zarkadoula, E; Iancu, D; Mihai, M D; Grygiel, C; Monnet, I; Kombaiah, B; Zhang, Y; Weber, W J
Abstract: The synergistic effect of nuclear ( S n ) and electronic ( S e ) energy loss observed in some ABO3 perovskites has attracted considerable attention due to the real possibility to modify various near-surface properties, such as the electronic and optical properties, by patterning ion tracks in the defective near-surface regions. In this study, we show that low-energy ion-induced disordering in conjunction with ionizing ion irradiation (18 MeV Si, 21 MeV Ni and 91.6 MeV Xe) is a promising approach for tailoring ion tracks in the near-surface of defective KTaO3 . Experimental characterization and computer simulations reveal that the size of these latent ion tracks increases with S e and level of pre-existing damage. These results further reveal that the threshold S e value ( S e th ) for track creation increases with decreasing pre-damage level. The values of S e th increase from 5.02 keV nm −1, for a pre-existing fractional disorder of 0.53 in KTaO3, to 10.81 keV nm −1 for pristine KTaO3 . Above these thresholds, amorphous latent tracks are produced due local melting and rapid quenching. Below a disorder fraction of 0.08 and S e ⩽ 6.68 keV nm −1, the synergistic effect is not active, and damage accumulation is suppressed due to a competing ionization-induced damage annealing process. These results indicate that, depending on S e and the amount of pre-existing damage, highly ionizing ions can either enhance or suppress damage accumulation in KTaO3, thus providing a pathway to tailoring defects states. Comprehending the conflicting roles of highly ionizing ions in defective ABO3 oxides is vital for understanding and predictive modeling of ion-solid interactions in complex oxides, as well as for achieving control over ion track size in the near-surface of defective KTaO3 .